Pengaruh Model Pembelajaran Cooperatif Integratif Reading And Composition (CIRC) Berbasis Video Animasi - Mutmainnah Mutmainnah; Ince Prabu Setiawan; Rizka Indahyanti (STKIP Andi Matappa Pangkep, 2023)
This study aims to describe the interests and learning outcomes of Indonesian Class II students at SDN 224 INP. Lekoboddong, using the Cooperative Integrated Reading and Composition (CIRC) method. The type of research used is experimental research. The population and sample used in this study used total sampling so that 25 students were obtained from the total number of students. The instrument used is a questionnaire of interest in learning and to determine student learning outcomes is a written test in the form of multiple choice questions in the form of pretest and posttest.Based on the results of the study, it was explained that the results of learning Indonesian in the percentage of the initial test (pretest) showed that students at school still got enough categories, namely 16 students with a percentage of 64%, then in the good category, 10 people with a percentage of 40%, while only 1 person in the very good category or 4%. While the results of the post test showed an increase in the good category as many as 16 people or 64% and the very good category also increased to 9 people or 36%.